TREATMENT ADHERENCE TO GUIDELINE EVALUATION IN T2D (TARGET-T2D) MALAYSIA: : IMPACT OF SGLT-2I USE AMONG PATIENTS WITH T2DM ATTENDING TERTIARY CARE - Ghani, Rohana Abdul; Noor, Nurain Mohd; Hussein, Zanariah; Raof, Anis Syazwani Abdul; Lim, Lee-Ling; Mustafa, Norlaila; Bebakar, Wan Mohd Wan; Samsuddin, Syahrizan; Bidin, Mohd Badrulhisham Long; Yong, Sy-Liang; et al. (Journal of the ASEAN Federation of Endocrine Societies, 2023)
INTRODUCTION Sodium-glucose cotransporter 2 (SGLT2) inhibitors have significant cardiovascular benefits, particularly in heart failure and chronic kidney disease.1,2 However, its use has been limited by its side effects and health system resources.3,4 Thus, TARGET-T2D was initiated to study the use of SGLT2i within our population to highlight the treatment gap between SGLT2i and non-SGLT2i users. We identified the differences between patients who received SGLT-2i and those who did not to highlight the importance of optimizing treatment in those who would benefit from the cardio- and renoprotective effects of SGLT2i. METHODOLOGY Cross-sectional data were collected at eight publiclyfunded tertiary hospitals in the Greater Kuala Lumpur region from December 2021 to June 2022). Patients aged ≥18 years with T2D treated with oral glucose-lowering drugs and/or injectable therapy who had two or more outpatient visits within the preceding year were eligible. Various demographic, anthropometric, and metabolic data were included for data analysis. Analyses were stratified by prior atherosclerotic cardiovascular disease (ASCVD) and clinic type (Diabetes specialist versus General medicine clinics). RESULTS Four thousand seven hundred three patients were recruited, of which 38% received SGLT2Is (n = 1803). Almost all of them attended the Endocrine Subspecialty clinic, whilst only 10% of the population received their prescriptions from the General Medical Clinic. Those who received SGLT2I were significantly younger (mean age 58.8 ± 11.6 vs 60.8 ± 12.9, p <0.001) with earlier onset of T2DM. They had greater metabolic risks including longer duration of T2DM, higher HbA1c, larger BMI and WC, with higher proportions of patients who had underlying atherosclerotic cardiovascular disease (ASCVD)(35.4% vs 30.1%, p = 0.01) and HHF 4.8% vs 3.5%, p <0.01). In addition, those who received SGLT2i demonstrated lower systolic and diastolic blood pressures and slightly better lipid profiles. However, there were lower proportions of patients who had eGFR <60 mL/min/1.73 m2 (25.8% vs 35.7%, p <0.001) and significant proteinuria with urinary albumin creatinine ratio (UACR) >3 mg/mmol (59.5% vs 63.8%, p = 0.021), among those who received SGLT2i versus the comparator group. Concerning treatment targets, attainment of individual and composite glycaemic, blood pressure, and lipid targets were significantly observed within the SGLT2I group versus the non-SGLT2i group. Multiple logistic regression models demonstrated that Endocrine clinic follow-ups, eGFR >45 mL/min/1.73 m2 , presence of ASCVD, and HHF are independent predictors for the use of SGLT2i within the study cohort. CONCLUSION Those who received SGLT2Is attended Endocrine Clinics and had the indications for its use including very high CV risks. However, a third of patients who did not receive the medication had the indications for it including the presence of ASCVD, eGFR <60 mL/min/1.73 m2 and significant proteinuria with urinary ACR >3 mg/mmol. This underscores the importance of including SGLT2i in the treatment regime for patients with T2DM.